COMPARATVE STUDY OF WORK LIFE BALANCE AMONG PRIVATE AND PUBLIC SECTOR BANKING EMPLOYEES IN PERAMBALUR DISTRICTBanking industry is an emerging industry in India, the entry of private sector and foreign banks have brought various essential changes in the ba - GEETHA, S.GEETHA; Rajendran, Dr R. (IJRDO - Journal of Applied Management Science, 2017)
Banking industry is an emerging industry in India, the entry of private sector and foreignbanks have brought various essential changes in the banking industry. The menace of work- lifeimbalance is noticeable in banking industry. Employees in the banks take painful effort to deliverthe various needs of its customers. Work deadlines are getting compact and the individual's jobsare loaded and added with quality output. Due to work in pressure, it becomes hard to maintainbalance between professional and family life. The output of the banking sector is dependent on thequality of human resources. The basic function of human resource development is to facilitateperformance improvement, measured in terms of finance indicators of operational efficiency andquality of financial services provided. The twin challenges faced by the banks' managements arethat of retaining the prevailing employees and providing a satisfying work environment for allemployees. The study attempts to find out the issues related with managing professional andpersonal life of employees in banking industry. The major objective of this paper is to identifyspecific issues and challenges in work life balance in banking industry and to suggest measures toimprove work life balance.